2018
DOI: 10.1055/s-0038-1627459
|View full text |Cite
|
Sign up to set email alerts
|

Primary Closure versus Bedside Silo and Delayed Closure for Gastroschisis: A Truncated Prospective Randomized Trial

Abstract: There were no differences seen between PC and DC in LOS, time to enteral feeds, or ventilator times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The findings of this systematic review of data from 120 studies including a large sample of US neonatal clinical trial participants (14 479 participants) support 3 important conclusions. First, Asian, Black, Hispanic, and Indigenous infants were underrepresented in these studies compared with our proxy for the US clinical NICU population.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The findings of this systematic review of data from 120 studies including a large sample of US neonatal clinical trial participants (14 479 participants) support 3 important conclusions. First, Asian, Black, Hispanic, and Indigenous infants were underrepresented in these studies compared with our proxy for the US clinical NICU population.…”
Section: Discussionmentioning
confidence: 53%
“…We assessed reporting by NIH funding: of the 52 studies funded by the NIH, 35 studies (67%) included race and ethnicity data. Among 68 studies not funded by the NIH, 40 studies (58%) reported race and ethnicity data; the difference between NIH-funded and non-NIH–funded studies was not statistically significant by Pearson χ 2 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Fraga et al indicated that primary closure, compared with silo placement, was associated with better outcomes, including the time to start enteral feeds, time to discontinue TPN, and hospital LOS [13]. However, Poola et al reported that there were no significant differences between primary closure and delayed closure with silo in hospital LOS, time to enteral feeding, and ventilator days [30]. Our study also found similar results when we compared patients who experienced primary closure and staged closure with silo.…”
Section: Discussionmentioning
confidence: 99%